Combining Light‐Gated and pH‐Responsive Nanopore Based on PEG‐Spiropyran Functionalization. Issue 2 (1st December 2017) - Ma, Tianji; Walko, Martin; Lepoitevin, Mathilde; Janot, Jean‐Marc; Balanzat, Emmanuel; Kocer, Armagan; Balme, Sebastien
Abstract: To mimic the selectivity and properties of biological channels and pumps, adaptive systems can be designed using artificial membranes. One big advantage of those membranes is that they are able to respond to several stimuli at the same time. Here, it is proposed to tailor conical nanopores by grafting polyethyleneglycol (PEG)‐spiropyrans in order to combine both light‐ and pH‐responsive properties. The study of the ionic transport reveals that after UV irradiation the nanopore is open while after visible irradiation, it is closed. This gating property is due to the self‐assembly of PEG‐spiropyran. The reversibility of the assembly inside the nanopore strongly depends on the solvent. Indeed, water blocks the photoswitchable molecule in its zwitterionic form, while ethanol favors the conformational switching. Under UV irradiation, the pH can control the nanopore selectivity. It is demonstrated that at acidic pH, the nanopore is selective to anion while at neutral pH the cation transport is favored. Abstract : This work aims to tune original light‐gated and pH response nanopore. To do so, PEG‐spiropyrans is grafted inside conical nanopores. The study of the ionic transport shows that light irradiation permits to control the nanopore opening and its pH selectivity. However the reversibility depends on solvent polarity due to the presence of PEG chain.